تأثير أسلوب اللعب المباشر في تعلم مهارتي الضربتين الارضيتين الامامية والخلفية بالتنس - خميس, ماجد خليل; زغير, رائد مهوس (Sulaimani Journal for Humanities, 2018)
The scientific development is regarded to be one of the important elements in developing the societies. This is in order to reach the highest levels and in different fields, especially in the athletic field, through using the modern techniques and serious styles in learning the basic skills intended by the scientists and specialists for developing the skills and the abilities of the learner. This represents the importance of the study in using the direct playing style for beginners and exploring its effect on learning. The problem of the study lies in using the symmetrical traditional styles in dividing the skills of the beginners and taking too long time in learning each part of those parts and then connecting them. This leads to losing excitement and motivation while waiting for a very long time till the parts are connected and chance to play is given. This creates boring and losing concentration in playing. This study aims at using the direct playing style for learning the skills of playing tennis for the beginners in the specialized schools in Baghdad. The researcher used the experimental method for learning the players of those schools. The sample is taken randomly. It is divided into two groups; the experiment and the control group. The experiment group used the direct playing style, while the experiment group used the traditional style of learning. The researcher adopted equivalence between the two groups, and then he conducted the pretests and applying the direct playing style in the protests. After dealing statistically, the researcher concluded that the direct playing style had a positive effect in learning the basic skills and this was used by the experiment group. The researcher recommends adopting this teaching technique for beginners for learning the basic skills in tennis.